IMPLEMENTING PHILOSOPHY-BASED LANGUAGE TEACHING APPROACH TO IMPROVE STUDENTS’ SPEAKING SKILL - Utary Rustam; Anwar Anwar; Amzah Amzah (ETERNAL (English, Teaching, Learning and Research Journal), 2018)
In university, in this case STAIN Parepare, the fourth semester students have been taught many kinds of speaking which varied based on different purposes. One of them is transactional speaking and Group Discussion is one of the kinds which frequently practised in college activity. In the initial study, it was found that students of the fourth semester in STAIN Parepare had low proficiency level in speaking and they had no motivation to participate in group discussion in speaking subjects. To overcome these problems, the writer implemented Philosophy-Based Language Teaching (PBLT) approach. This approach was selected to enhance students’ thinking ability in group discussion in order that they build an idea then convey it to improve their speaking skill. This research was quantitative which employed pre-experimental research with one group pretest-posttest design. The data was collected by speaking test and observation then processed by statistical calculation by t-test nonindependent sample. Furthermore, the findings of this result revealed that PBLT approach is able to improve students speaking skill. Besides, this approach improved students’ speaking skill through the existence of philosophical questions which allowed the discussion surrounded by active participation of group members. In addition, the findings indicated students’ improvement in speaking skill both intellectual and social aspect. Finally, this research provided some suggestions to overcome some problems found during this research.